Off-the-record target zones: Theory with an application to Hong Kong's currency board - Yu-Fu Chen; Michael Funke; Nicole Glanemann (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
This paper provides a modelling framework for evaluating the exchange rate dynamics of a target zone regime with undisclosed bands. We generalize the literature to allow for asymmetric one-sided regimes. Market participants' beliefs concerning an undisclosed band change as they learn more about central bank intervention policy. We apply the model to Hong Kong's one-sided currency board mechanism. In autumn 2003, the Hong Kong dollar appreciated from close to 7.80 per US dollar to 7.70, as investors feared that the currency board would be abandoned. In the wake of this appreciation, the monetary authorities finally revamped the regime as a symmetric two-sided system with a narrow exchange rate band.
URN:NBN:fi:bof-201408072139
Keywords: C61; E42; F31; F32; 330; Currency Board Arrangement; Target Zone Model; Hong Kong